Environmental, Chemical and Medical Sensors - Bhattacharya, Shantanu; Agarwal, Avinash Kumar; Chanda, Nripen; Pandey, Ashok; Sen, Ashis Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book covers the fundamentals of sensor technologies as well as the recent research for the development of environmental, chemical and medical sensor technologies. Chapters include current research on microflow cytometry, microfluidic devices, colorimetric sensors, and the development of low-cost optical densitometric sensors and paper based analytical devices for environmental and biomedical applications. Special focus has been given to nanotechnology and nanostructures- their fabrication, uses and utility in different fields of research such as for the design of tools for medical diagnostics, therapeutics, as well as for detection and estimation of pollutant levels in water and air quality monitoring. This book is intended as a resource for researchers working in the field of sensor development across the world. .
Part I General -- 1. Introduction to Environmental, Chemical and Medical Sensors -- Part II Environmental Sensors -- 2. Sensors for air monitoring -- 3. Gold Nanostructure in sensor technology: Detection and estimation of chemical pollutants -- 4. Impedimetric Sensors in environmental analysis: An overview -- Part III Chemical Sensors -- 5. Inkjet Printed Sensors on Flexible Substrates -- 6. Sensing using microfluidic platform -- 7. Green Synthesized Nanoparticles as Potential Nanosensors -- Part IV Medical Sensors -- 8. Fabrication of nanostructures with bottom-up-approach and their utility in diagnostics, therapeutics and others -- 9. Miniaturized Sensors and Actuators for Biological Studies on Small Model Organisms of Disease -- 10. Polymeric Patterned Surface for Biomedical Applications -- 11. Nanoparticles based Diagnostics -- 12. Designing of a Low-Cost Optical Density Meter for Medical Applications -- 13. Flexible Sensors for Biomedical Application -- 14. Low-cost paper analytical devices for environmental and biomedical sensing applications -- 15. DNA based sensors -- 16. The Microflow Cytometer -- 17. Microfluidic Sensors for Mechanophenotyping of Bio-logical Cells.
Keywords: Electronic circuits; Biomedical engineering; Environmental engineering; Biotechnology; Bioremediation; Electronic Circuits and Systems; Biomedical Engineering and Bioengineering; Environmental Engineering/Biotechnology.